Identification of Research Paradigms for Managing the Cricketing Ecosystem Using Stakeholder Analysis and Text Mining. (August 2021) - Ray, Subhasis
It took almost 400 years for test cricket to start off, and thereafter it just took 94, 34 and 13 years for the introduction of ODI, T20I and T10 formats, respectively. Length of the formats is shrinking over time at an alarming rate. If the trend continues, the format of five overs or less may not be far away and cricket pundits are fearing that the longest format, that is, test cricket, may lose its relevance. Unfortunately, the management part of the cricketing ecosystem has not drawn much attention from the academic world. Since market dynamics is playing a vital role in decision-making post commercialization of the cricket, this study applies stakeholder analysis and identifies three key stakeholders, namely administrators, players and spectators, and their aspirations. It suggests a shift from the ICC-led hierarchical model to the horizontal and more democratic model for sports governance during the post-commercialization stage. The results of the study indicate that even though ICC had taken a number of measures for advancement of the sport during 2015–2018, many of them are criticized like the world test championship or day-night test matches. The study scrapes through opinions of cricket-related professionals from open sources, applies sentiment analytics to classify them, uses text summarization to extract summary viewpoints and rates them on unanimity scale. A comparison is made between the actions taken by ICC and the pool of unanimous viewpoints using evidence-based assessment (EBA). Finally, it develops a framework of six research paradigms, taking into account the stakeholders' aspirations and the EBA outcome. If these paradigms are acted upon, it can ensure convergence of stakeholders' goals and balance in the cricket mix. Additionally, if ICC can make unanimous viewpoints from its stakeholders a part of its future plan, acceptability of its decisions will be more.